PELATIHAN DESAIN BATIK BERPOLA UNTUK GAMIS DI USAHA SENTRA BATIK MELATI SUMENEP - Islamiyah, Suri Intan; Inang, Yuhri; Nahari, Inty; Rahayu, Imami Arum Tri (Jurnal Socia Akademika, 2023)
The background to this research is that there is a large demand for patterned batik cloth for making gamis clothing, while there is not yet enough patterned batik material available for making gamis clothes. The length of batik produced at this center is limited, namely 2 meters to 2.25 meters. Meanwhile, making a robe requires a minimum of 3 meters of fabric. The solution previously offered was to buy two pieces of patterned batik cloth to make robes. However, this is considered excessive and wasteful. The aim of this research is to provide an alternative solution to the problem regarding the need for batik cloth for making robes without having to look for motifs, namely through patterned batik design training for robes which will equip each craftsman. This type of research uses pre- experimental with a one-shot case study pattern. The results of the training to design patterned batik for robes received a score of 88% in the good category. The resulting patterned batik design for robes scored 83.3 in the very good category. The questionnaire from the responses of batik craftsmen or training participants received a score of 74.5% in the good category